Layered graphene/hexagonal boron nitride nanosheets (Gr/h-BNNs) applied to the CO2 photoconversion into methanol. (December 2022) - Gomes, Paulo V.R.; Azeredo, Nathalia F.B.; Garcia, Luis M.S.; Zambiazi, Priscilla J.; Morselli, Giovanni R.; Ando, Rômulo A.; Otubo, Larissa; Lazar, Dolores R.R.; de Souza, Rodrigo F.B.; Rodrigues, Debora F.; Neto, Almir O.
Highlights: Layered Graphene/Hexagonal Boron Nitride Nanosheets (Gr/ h- BNNs) applied to the CO2 reduction. CO2 photoconversion into Methanol. h -BN and graphene gave the material promising and adjustable optical properties. Abstract: Photocatalysts based on heterostructure 2D materials show promising properties for the construction of optoelectronic devices for selective reduction of CO2 to methanol. In this sense, a fast and simple method to produce 2D hexagonal hybrid BN nanosheets ( h -BNNs) doped with graphene heterostructure by van der Waals interactions was developed. The method used plasma created by a Tesla coil. The Gr/ h -BNNs hybrid material obtained presented a stacking structure containing h -BNNs and graphene layers. The structure included doping of carbon atoms along the h -BN edge structures. The doping of the h -BN nanostructure with graphene sheets, conferred adaptable optical properties to the semiconductor, resulting in band gap energy values favorable to photocatalysis. The reaction promoted selective reduction of CO2 to methanol, and synthesis of other products, such as formaldehyde and formic acid, due to multielectronic transfer processes. Graphical abstract: Image, graphical abstract